Research on Smart Community Construction from the Perspective of Agile Governance - Lin, Gao (International Journal of Social Sciences and Public Administration, 2024)
The concept of smart communities emphasizes the synergistic effects between decision-making at the computational level and service delivery, which aligns perfectly with the notion of ‘agile governance’. Leveraging ‘agile governance’ as an analytical framework for the study of smart community construction, this paper decomposes the construction of smart communities supported by big data analytics technology into four aspects: balancing multiple objectives, collaborative governance among stakeholders, efficiency of tool transformation, and adaptability propagation. It also proposes relevant suggestions for constructing a community agile governance model based on smart community technology platforms, aiming to achieve efficient, intelligent, and sustainable development of community governance.